Evaluation of regulatory and practices on disclosure for Sukuk in Saudi Arabia - Al-Harbi, Abdullah Dhaidan; Ab Rahman, Suhaimi (AESS Publications, 2018)
Financial market authorities demand participants in the market to disclose relevant information to the public. So that to prevent the utilization of individuals, less informed, and minority investors by exporting companies, in the ground of Islamic capital markets, particularly in sukuk markets, in order to achieve the bargain by applying the principle of avoiding excessive uncertainty and reducing asymmetry information between different parties in the sukuk contract, where disclosure of specific information is required by Islamic law authorities. Certainly this disclosure is the first layer to protect investor and consumer. Information relating to Sukuk investment is disclosed not only at the time of issue but also thereafter. This is a special trend of the sukuk market. The main objective of this paper is to assess the disclosure regulations within the presentation process and the secondary market activities of sukuk in Saudi Arabia.